One-pot, microwave-assisted synthesis of polymethylene-bridged bis(1H-1,2,4triazol-5(3)-amines) and their tautomerism - Phei, Felicia Lin Lim; Lee, Ming Hu; Tiekink, Edward R. T. *; Dolzhenko, Anton V (Elsevier, 2018)
A highly selective and efficient method for the synthesis of 3,3’(5,5’)-polymethylene-bis(1H1,2,4-triazol-5(3)-amines) was developed using the reaction of dicarboxylic acids and aminoguanidine in an aqueous medium. This one-pot, microwave-promoted method was proved to be scalable affording the desired products in good yields and purity. The scope of the method was successfully explored by the preparation of a small library of polymethylene-bis(1H-1,2,4-triazol-5(3)-amines) with different alkyl chain linkers. The annular prototropic tautomerism in the prepared compounds was studied using NMR spectroscopy and X-ray crystallography.